Continuous in-the-field measurement of heart rate: Correlates of drug use, craving, stress, and mood in polydrug users. (1st June 2015) - Kennedy, Ashley P.; Epstein, David H.; Jobes, Michelle L.; Agage, Daniel; Tyburski, Matthew; Phillips, Karran A.; Ali, Amin Ahsan; Bari, Rummana; Hossain, Syed Monowar; Hovsepian, Karen; Rahman, Md. Mahbubur; Ertin, Emre; et al.
Highlights: High-quality heart-rate data can be obtained from drug users in the field. Drug craving is associated with increased heart rate in the natural environment. Dose-related effects of cocaine on heart rate were detectable in the field data. Abstract: Background: Ambulatory physiological monitoring could clarify antecedents and consequences of drug use and could contribute to a sensor-triggered mobile intervention that automatically detects behaviorally risky situations. Our goal was to show that such monitoring is feasible and can produce meaningful data. Methods: We assessed heart rate (HR) with AutoSense, a suite of biosensors that wirelessly transmits data to a smartphone, for up to 4 weeks in 40 polydrug users in opioid-agonist maintenance as they went about their daily lives. Participants also self-reported drug use, mood, and activities on electronic diaries. We compared HR with self-report using multilevel modeling (SAS Proc Mixed). Results: Compliance with AutoSense was good; the data yield from the wireless electrocardiographs was 85.7%. HR was higher when participants reported cocaine use than when they reported heroin use ( F (2, 9) = 250.3, p < .0001) and was also higher as a function of the dose of cocaine reported ( F (1, 8) = 207.7, p < .0001). HR was higher when participants reported craving heroin ( F (1, 16) = 230.9, p < .0001) or cocaine ( F (1, 14) = 157.2, p < .0001) than when they reported of not craving. HR was lower ( p < .05) in randomly prompted entries in which participants reported feeling relaxed, feeling happy, or watching TV, and was higher when they reported feeling stressed, being hassled, or walking. Conclusions: High-yield, high-quality heart-rate data can be obtained from drug users in their natural environment as they go about their daily lives, and the resultant data robustly reflect episodes of cocaine and heroin use and other mental and behavioral events of interest.